A critical study of classical religious texts in global contexts: challenges of a changing world - Elness-Hanson, Beth E.; Skarpeid, Jon (Peter Lang, 2019)
A Critical Study of Classical Religious Texts in Global Contexts: Challenges of a Changing World challenges toxic stereotypes of world religions by providing scholarly investigations into classic sacred texts in global contexts. By engaging more perspectives, important connections, and more, complex and humanizing "stories" are developed, inviting the reader to see the face of the "Other" and, perhaps, to see a bit of oneself in that face. In today’s world of increasing polarization and the rise of nationalism, the contributors to this volume welcome the reader to join them in a shared humanity that seeks understanding. A red thread that runs through each chapter relates to the challenges that globalization brings to the sacred texts in various contextual settings. The contributors describe various circumstances related to reading and interpreting sacred writings—whether historical or more recent—which continue to have an influence today. The essays in this volume view these religious texts in relation to four dichotomies: minority-majority, diaspora-homeland, center-periphery of the globalized world, and secular-religious. These elements by no means exhaust the issues, but they serve as a starting point for a discussion of relevant contexts in which sacred texts are read. The breadth of research represented stimulates a deeper understanding that is vital if we are to move beyond stereotypes and religious illiteracy to meaningfully engage the "Other" with wisdom and empathy—important virtues in today’s world. A Critical Study of Classical Religious Texts in Global Contexts will appeal to scholars and graduate students of religious studies, sacred scriptures, and post-colonial studies, as well as informed and inquisitive general readers interested in exploring interfaith dialogue and broadening their religious literacy.